Phase 1 dose-escalation study of a novel oral PI3K/mTOR dual inhibitor, LY3023414, in patients with cancer - Kondo, Shunsuke (Invest New Drugs, 2020)
LY3023414 is an oral, selective adenosine triphosphate-competitive inhibitor of class I phosphatidylinositol 3-kinase isoforms, mammalian target of rapamycin, and DNA-protein kinase in clinical development. We report results of a 3 + 3 dose-escalation Phase 1 study for twice-daily (BID) dosing of LY3023414 monotherapy in Japanese patients with advanced malignancies. The primary objective was to evaluate tolerability and safety of LY3023414. Secondary objectives were to evaluate pharmacokinetics and to explore antitumor activity. A total of 12 patients were enrolled and received 150 mg (n = 3) or 200 mg (n = 9) LY3023414 BID. Dose-limiting toxicities were only reported at 200 mg LY3023414 for 2 patients with Grade 3 stomatitis. Common treatment-related adverse events (AEs) across both the dose levels included stomatitis (75.0%), nausea (66.7%), decreased appetite (58.3%), diarrhea, and decreased platelet count (41.7%), and they were mostly mild or moderate in severity. Related AEs Grade ≥ 3 reported for ≥1 patient included anemia, stomatitis, hypophosphatemia, and hyperglycemia (n = 2, 16.7%). Two patients discontinued due to AEs (interstitial lung disease and stomatitis). No fatal events were reported. The pharmacokinetic profile of LY3023414 was characterized by rapid absorption and elimination. Five patients had a best overall response of stable disease (150 mg, n = 3; 200 mg, n = 2) for a 55.6% disease control rate. LY3023414 up to 200 mg BID is tolerable and safe in Japanese patients with advanced malignancies.